Safeguarding the Backbone of Modern Society: Cybersecurity Strategies for Critical Infrastructure in the Digital Age - Alok Sarkar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the cybersecurity challenges and strategic approaches for protecting critical infrastructure in an increasingly digitized world. The article analyzes the evolving threat landscape exemplified by watershed incidents like the Colonial Pipeline ransomware attack and the Ukraine power grid compromise, revealing how digital attacks can cascade into physical and economic disruptions. It explores unique vulnerabilities of Industrial Control Systems and Operational Technology environments, including legacy system limitations, IT/OT convergence risks, and specialized protocol weaknesses. Innovative defense strategies leveraging artificial intelligence, zero trust architecture, and blockchain applications are evaluated alongside resilience engineering practices that enable critical systems to withstand compromise while maintaining essential functions. The article extends to regulatory frameworks and public-private collaboration models that establish security baselines and facilitate information sharing. Finally, emerging challenges including quantum computing threats, 5G/6G expansion, AI-powered offensive capabilities, and climate change impacts are addressed with forward-looking recommendations to secure the foundational systems upon which modern society depends.
Keywords: Critical Infrastructure Protection; Industrial Control Systems; Zero Trust Architecture; Resilience Engineering; Public-Private Collaboration